The effect of discussion classes on students’ overall performance at an Institute for Open and Distance Learning in South Africa : analysis using mixed-effects models - Letsoalo, Maupi Eric; Makgakga, Tšhegofatšo (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
Most ODL students have had little to no exposure to the ODL environment. Therefore, institutions must assess the impact of existing support mechanisms, such as discussion classes, aimed at assisting students to succeed in the program. This exploratory quantitative study evaluated the overall effect of discussion classes on undergraduate mathematics education student academic performance. Students who registered for Measurement in Intermediate and Senior Mathematics in the 2018 academic year at the University of South Africa constituted a study population. Both crude and adjusted mixed-effects models indicated that those who attend and those who did not attend discussion classes performed insignificantly differently. However, the reduction of the estimate after adjusting for assignment score is educationally important and it has presented an opportunity to re-evaluate the importance of the intervention strategies. This paper suggested that student support in ODL has the potential to improve student success rates. Also, the interventions should be guided by an informed choice of philosophies that underpins the rationale for open and distance learning. A further in-depth study is needed to understand how various aspects of student support contribute to success in open and distance learning. Understanding student support services, their contribution, and importance from the perspective of university administration and all stakeholders may aid ODL policymakers in formulating policies and strategies for student academic assistance, as well as offering the necessary guidance to improve service quality.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022)
Keywords: Discussion classes; Affective factors; Support strategy; Academic performance; Distance learning; Open learning; Open learning; Distance education students; Distance education -- South Africa; Academic achievement -- Africa